A three-dimensional semi-quantitative method to monitor the evolution of polycyclic aromatic hydrocarbons from vacuum gas oil feedstocks to lighter products. (15th July 2021) - Reymond, Carole; Le Masle, Agnès; Colas, Cyril; Charon, Nadège
Graphical abstract: Highlights: Methodology for semi-quantification of PAHs in VGOs. Characterisation of six VGOs with well-organised CPC × SFC chromatograms. Evolution of PAH concentration from native VGO feedstocks to hydrotreated products. Abstract: Formation and accumulation of polycyclic aromatic hydrocarbons (PAHs) are responsible of major topical issues related to the conversion of petroleum vacuum gas oils (VGOs) in transportation fuels through hydrocracking process. To achieve an efficient management of these hydrocarbons, a detailed semi-quantitative description of PAHs contained in VGOs was provided by a three-dimensional off-line analytical approach based on centrifugal partition chromatography (CPC), supercritical fluid chromatography (SFC) and high-resolution mass spectrometry (HRMS). As a result, well-organised CPCxSFC chromatograms provided a relevant separation of PAHs according to both unsaturation level (DBE) and alkylation degree. This dedicated methodology allowed the semi-quantification of PAHs having a DBE superior to 12. For the first time, PAHs were quantified in six VGOs allowing to highlight differences in composition depending on the origin of the samples. Then, the evolution of PAH concentration was monitored during hydrotreating and hydrocracking processes. For the hydrotreated/hydrocracked (HDT/HCK) products, their sulphur and nitrogen contents were low enough to make possible semi-quantification of PAHs directly by SFC/HRMS. An accumulation of PAHs was observed when a recycle stream from the unconverted oil to HDT reactor was applied. This work demonstrates that valuable analytical data could be obtained leading a step forward in the overall understanding of a process from native VGO feedstocks to the HDT/HCK products.